2017
DOI: 10.1002/2016wr019208
|View full text |Cite
|
Sign up to set email alerts
|

Variational assimilation of streamflow data in distributed flood forecasting

Abstract: Data assimilation has the potential to improve flood forecasting. However, research efforts are still needed for an effective development of assimilation schemes suitable for operational usage, especially in case of distributed hydrologic models. This work presents a new assimilation system of streamflow data from multiple locations in a distributed hydrologic model. The system adopts a mixed variational‐Monte Carlo approach, and is here tested with the hydrologic model MOBIDIC, that is part of the operational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 87 publications
2
31
0
Order By: Relevance
“…Ercolani and Castelli, 2017); moreover, the reliability of data from traditional sensors outperforms that of CSD. Hence, from a practical point of view, CSD have limited usefulness at locations already equipped with traditional sensors.…”
Section: The Use Of Real Csd In Operational Flood Forecastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ercolani and Castelli, 2017); moreover, the reliability of data from traditional sensors outperforms that of CSD. Hence, from a practical point of view, CSD have limited usefulness at locations already equipped with traditional sensors.…”
Section: The Use Of Real Csd In Operational Flood Forecastingmentioning
confidence: 99%
“…Several studies indicated that the information content in a rainfall-runoff record is sufficient to support models of only very limited complexity (Jakeman and Hornberger, 1993;Refsgaard, 1997). This im-plies that distributed, or semi-distributed, hydrological models are seldom calibrated; rather, they are commonly overparametrized, since calibration rarely involves their internal states (Sebben et al, 2012;Viero et al, 2014).…”
Section: The Use Of Real Csd In Operational Flood Forecastingmentioning
confidence: 99%
“…Advanced methods of data assimilation are an option for an optimal combination of information from models that are inherently imperfect, with also uncertain observations, thus obtaining estimates that are physically consistent with the reduction and quantification of the uncertainties (MCLAUGHLIN, 1995;EL SERAFY, 2006;GUPTA, 2007;CLARK et al, 2008;REICHLE, 2008;LIU et al, 2012;RIDLER et al, 2014;ERCOLANI;CASTELLI, 2017). Initially these methods were more popular in earth sciences for meteorological forecasting, characterization of atmospheric and oceanic conditions; however, in recent years they have been adapted for hydrological and hydraulic applications (LIU et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Data assimilation methods with applications of discharge data into distributed hydrological models are more abundant (WEERTS; EL SERAFY, 2006;CLARK et al, 2008;RAKOVEC et al, 2012;CHEN et al, 2012;DECHANT;CHEN et al, 2013;DUMEDAH;COULIBALY, 2013;ZHANG et al, 2014;MORADKHANI et al, 2005a;MORADKHANI et al, 2005b;SEO et al, 2009;ZHANG, 2010;PAUWELS;DE LANNOY, 2009;ERCOLANI;CASTELLI, 2017). However, recent advances in remote sensing encouraged the use of observations such as radar altimetry to estimate river levels (PAIVA et al, 2013b;ANDREADIS et al, 2007;BIANCAMARIA et al, 2011), microwave radiation to estimate soil humidity (NAGARAJAN et al, 2011;YAN;MORADKHANI, 2016), remote observation to infer the properties of snow as an extension of large scale coverage (ANDREADIS; LETTENMAIER, 2006), among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation